Test cricket: A history - Wigmore, Tim (London Quercus, 2025)
The first narrative history of Test cricket as it nears its 150th birthday, telling the story of how the game has evolved since 1877, told through the moments and personalities that have shaped the format. With a focus on the game and its broader significance alike Tim Wigmore gives Test cricket its historical and social context, whilst reminding us that it's unrivalled as a fascinating sporting spectacle. Meticulously researched and told with the passion of an award-winning writer, Test Cricket is also illuminated by a series of gripping fresh interviews with more than forty stars of international test cricket.
Keywords: Cricket; Test Cricket